Pook bantayan ; Behind Batibot ; In their image [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Private sector manned intersections to solve traffic problems. A U.P. study reveals that many Filipino children wat to be Americans, Japanese even Saudi Arabians. The success of "Batibot show" in translating Filiipino values to Filipino children and what goes on behind the scene.